Pengaruh Lama Pengeringan Jamur Tiram (Pleurotus ostreatus) Menggunakan Gelombang Mikro Terhadap Rendemen Tingkat Kekerasan dan Warna - Adhiguna, Rizky Tirta Adhiguna (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This study aims to determined the effect of drying time of oyster mushrooms (Pleurotus ostreatus) using a microwave oven on yield, hardness, and color. The method used is an experimental design with a completely randomized design consisting of two treatment factors, namely the type of oyster mushroom (white oyster mushroom and HU oyster mushroom) and drying time (20 minutes, 30 minutes, and 40 minutes). The results showed that drying time significantly affected the three parameters tested (p<0.05). The highest yield was obtained with 20 minutes of drying for white oyster mushrooms at 41%, while the lowest yield was with 40 minutes of drying for HU oyster mushrooms at 7.52%. The highest hardness was achieved with 30 minutes of drying for white oyster mushrooms at 256.8 gf, and the lowest with 20 minutes of drying at 83.3 gf. The color of the oyster mushrooms was also affected by drying time, with the highest lightness value at 20 minutes of drying for white oyster mushrooms at 63.87%. Based on the results, the best drying time to produce oyster mushrooms with optimal quality is 20 minutes